The Presence 5 for Racial Justice Framework for anti‐racist communication with Black patients. (18th July 2022) - Brown‐Johnson, Cati; Cox, Joy; Shankar, Megha; Baratta, Juliana; De Leon, Gisselle; Garcia, Raquel; Hollis, Taylor; Verano, Mae; Henderson, Kelsey; Upchurch, Mauranda; Safaeinili, Nadia; Shaw, Jonathan Glazer; et al.
Abstract: Objective: To identify communication practices that clinicians can use to address racism faced by Black patients, build trusting relationships, and empower Black individuals in clinical care. Data Sources: Qualitative data ( N = 112 participants, August 2020–March 2021) collected in partnership with clinics primarily serving Black patients in Leeds, AL; Memphis, TN; Oakland, CA; and Rochester, NY. Study Design: This multi‐phased project was informed by human‐centered design thinking and community‐based participatory research principles. We mapped emergent communication and trust‐building strategies to domains from the Presence 5 framework for fostering meaningful connection in clinical care. Data Collection Methods: Interviews and focus group discussions explored anti‐racist communication and patient–clinician trust ( n = 36 Black patients; n = 40 nonmedical professionals; and n = 24 clinicians of various races and ethnicities). The Presence 5 Virtual National Community Advisory Board guided analysis interpretation. Principal Findings: The emergent Presence 5 for Racial Justice (P5RJ) practices include: (1) Prepare with intention by reflecting on identity, bias, and power dynamics; and creating structures to address bias and structural determinants of health; (2) Listen intently and completely without interruption and listen deeply for the potential impact of anti‐Black racism on patient health and interactions with health care; (3) Agree on what matters most by having explicit conversations about patient goals, treatment comfort and consent, and referral planning; (4) Connect with the patient's story, acknowledging socioeconomic factors influencing patient health and focusing on positive efforts; (5) Explore emotional cues by noticing and naming patient emotions, and considering how experiences with racism might influence emotions. Conclusion: P5RJ provides a framework with actionable communication practices to address pervasive racism experienced by Black patients. Effective implementation necessitates clinician self‐reflection, personal commitment, and institutional support that offers time and resources to elicit a patient's story and to address patient needs.